Magnesium fertilisation enhanced forage yield primarily in tetraploid perennial ryegrass (Lolium perenne L.) - Rene Aavola; Anne Ingver; Evelin Loit-Harro; Tanel Kaart; Pille Sooväli; Inga Hiiesalu; Ilmar Tamm (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2025)
Magnesium (Mg) plays a crucial role in determining the yield and forage quality of perennial ryegrass (Lolium perenne L.), and its deficiency can impair animal health, however its effect remains underexplored, in several regions where Mg deficiency is common. This study, conducted in the northern region, investigated the impact of Mg fertilisation on dry matter (DM) yield, feeding value, and disease resistance in cultivars differing in ploidy and maturity. Our results showed that Mg treatment significantly enhanced DM yield and resistance to crown rust (Puccinia coronata Corda), but increased acid detergent fibre concentration thereby decreasing digestibility and metabolisable energy concentration. Tetraploids produced higher crude protein (CP) yield but lower CP concentration compared to diploids. Nonetheless, tetraploids exhibited superior DM yield, digestibility, energy concentration, and intake potential. In addition, tetraploids were more resistant to all the observed diseases: leaf spot (Drechslera siccans (Drechsler) Shoemaker), crown rust and snow mold (Microdochium nivale). Our research addresses the existing knowledge gap regarding the impact of Mg fertilisation on perennial ryegrass production and wider adoption of this valuable forage crop in more northern regions. We recommend to use Mg fertiliser in production of perennial ryegrass even when only moderate deficiency in the soil is observed.